###### Asked in Uncategorized

Uncategorized

# How do you Simplify (X-2) (2x 4)?

**We need you to answer this question!**

###### If you know the answer to this question, please register to join our limited beta program and start the conversation right now!

## Related Questions

###### Asked in Math and Arithmetic, Algebra

### What is x2 4x 4?

###### Asked in Algebra

### X2 plus 2x - 14 equals 6?

###### Asked in Math and Arithmetic, Algebra, Calculus

### When x3 plus 3x2-2x plus 7 is divided by x plus 1 what is the remainder?

(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)
(multiply x + 1 by x2, and subtract the product from the
dividend)
1. x2(x + 1) = x3 + x2
2. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2
= 2x2 - 2x + 7
(multiply x + 1 by 2x, and subtract the product from 2x2
- 2x + 7)
1. 2x(x + 1) = 2x2 + 2x
2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x =
-4x + 7
(multiply x + 1 by -4, and subtract the product from -4x
+ 7)
1. -4(x + 1) = -4x - 4
2. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11
(remainder)

###### Asked in Math and Arithmetic, Algebra, DIY Projects

### How do you slove this problem 3x-111 x2 x?

There are some operators missing that make this rather
ambiguous.
If you mean:
3x - 111 + x2 = x
and wish to solve for x, then here's the answer:
x2 + 2x - 111 = 0
x2 + 2x + 1 = 112
(x + 1)2 = 112
x + 1 = ± √112
x = -1 ± 4√7
If you mean:
3x - 111 = x2 + x
Then solving for x gives us this:
x2 - 2x + 111 = 0
x2 - 2x + 1 = 112
(x - 1)2 = 112
x - 1 = ± √112
x = 1 ± 4√7
If you mean:
3x - 111 + x2 + x
And want to simplify it, that would be:
x2 + 4x - 111
Not much really, as it can't be factored further.